Media studies : texts, institutions and audiences - Taylor, Lisa.; Willis, Andrew (Malden, MA : Blackwell, 1999)
This book is devided into three parts - on texts, institutions and audiences - covering the major approaches to the media studies.
Keywords: Mass media; Television broadcasting; Television broadcasting; Mass media; Motion pictures